Analysis of the Financial Performance of the Provincial Government of Bangka Belitung Islands 2020-2022 - Meidina, Catherine; Wenni Anggita; Vebtasvili (Jurnal Riset Mahasiswa Akuntansi, 2024)
This study aims to analyze the financial performance of Bangka Belitung Province from 2020 to 2022, focusing on the Ratio of , Locally-Generated Revenue Effectiveness, Harmony Ratio, Degree of Fiscal Independence Ratio, Degree of Dependency Ratio, and Degree of Fiscal Decentralization Ratio. This descriptive quantitative research uses data obtained from the website of the Bangka Belitung Provincial Financial Agency through documentation methods. Data analysis is conducted by calculating these financial ratios. The results show that the Ratio of Locally-Generated Revenue Effectiveness is very effective. The Harmony Ratio is not harmonious because most of the budget is still focused on operational expenses. The Degree of Fiscal Independence Ratio is moderate with a participatory relationship pattern, the Degree of Dependency Ratio is very high, and the Degree of Fiscal Decentralization Ratio falls into the sufficient category, indicating progress in fiscal decentralization.